Analisis Peran Bawaslu Provinsi Jawa Timur dalam Pengawasan Netralitas ASN pada Pemilihan Umum - Bryan Febryanto; Diana Hertati (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
General elections are a form of a country's democratic system. The General Election Supervisory Body is one of the agencies in organizing general elections which is responsible for supervising general elections so that they run honestly and fairly. This research aims to determine the role of the East Java Province Bawaslu in monitoring the neutrality of the State Civil Apparatus in the Election. The method used in this research is descriptive qualitative with data collection techniques through observation, interviews and documentation. Analysis of this research data uses the theory put forward by Sururama and Amalia (2020:44) explaining the stages of supervision which consist of setting implementation standards, determining measurement of activity implementation, comparing activity implementation with standards and analyzing deviations, and taking corrective action. The research results show that there is SKB Number 2 of 2022 concerning Guidelines for the Neutrality Development and Supervision of State Civil Service Employees in the Implementation of General Elections and Elections. Apart from that, Bawaslu also held declaration activities to increase the neutrality of ASN during the election and take action against violations that occurred according to the rules.